Ontology Tool Benchmarks and Their Construction - Zamazal, Ondřej (2019)
The goal of the habilitation thesis was to support an availability of the ontology benchmarks for various ontology tools on Semantic Web. The habilitation thesis contains five chapters. First chapter explains the main concepts of Semantic Web, ontology tools and their benchmarking. The next chapters contribute to the realization of the habilitation thesis goal. The second chapter deals with the exploration of ontology benchmarks and their characterization along with the creation of recommender tool aimed at recommending ontology benchmark for given ontology tool and its benchmarking needs. The third chapter describes the creation, maintenance and enhancements of the OntoFarm ontology benchmark from the conference organization domain with primary target at ontology matching. The fourth chapter introduces the tool for supporting a construction of ontology benchmarks, OOSP (Online Ontology Set Picker). Finally, the fifth chapter describes the automatic platforms for ontology tool testing and the OntoFarm deployment on the HOBBIT platform.